Decision Support System for PNBP Proposal Selection Using the Simple Multi-Attribute Rating Technique - Suhada, Intan; Putra, Fajri Profesio (Politeknik Negeri Lhokseumawe, 2025)
Non-Tax State Revenue (PNBP) is one of the key funding sources at Politeknik Negeri Bengkalis, managed by the Center for Research and Community Service (P3M). The proposal selection process often encounters issues related to objectivity and transparency. This study aims to develop a Decision Support System (DSS) based on the Simple Multi-Attribute Rating Technique (SMART) method to improve the efficiency and accuracy of proposal selection. The system wasdeveloped as a web-based application and tested on 12 proposals. The evaluation criteria include Problem Formulation, Research Output Potential, Research Methodology, Literature Review, and Research Feasibility. The test results showed a compatibility rate of 83.33%,where 10 proposals had identical rankings, and 2 proposals differed by one rank compared to manual assessments by P3M. The scoring was conducted through weight normalization, utility value calculation, and final score aggregation. System evaluation using the Blackbox Testingmethod demonstrated that all core functions operated correctly for three user types (admin, reviewer, and user) without any detected errors. The system successfully produces selection results that closely match real-world conditions and contributes to enhancing objectivity, transparency, and the overall quality of the PNBP proposal selection process.